R26‐WntVis reporter mice showing graded response to Wnt signal levels. (31st March 2016) - Takemoto, Tatsuya; Abe, Takaya; Kiyonari, Hiroshi; Nakao, Kazuki; Furuta, Yasuhide; Suzuki, Hitomi; Takada, Shinji; Fujimori, Toshihiko; Kondoh, Hisato
Abstract : The canonical Wnt signaling pathway plays a major role in the regulation of embryogenesis and organogenesis, where signal strength‐dependent cellular responses are of particular importance. To assess Wnt signal levels in individual cells, and to circumvent the integration site‐dependent bias shown in previous Wnt reporter lines, we constructed a new Wnt signal reporter mouse line R26‐WntVis. Heptameric TCF/LEF1 binding sequences were combined with a viral minimal promoter to confer a graded response to the reporter depending on Wnt signal strengths. The histone H2B‐EGFP fusion protein was chosen as the fluorescent reporter to facilitate single‐cell resolution analyses. This WntVis reporter gene was then inserted into the ROSA26 locus in an orientation opposite to that of the endogenous gene. The R26‐WntVis allele was introduced into Wnt3a −/− and Wnt3a vt/− mutant mouse embryos and compared with wild‐type embryos to assess its performance. The R26‐WntVis reporter was activated in known Wnt‐dependent tissues and responded in a graded fashion to signal intensity. This analysis also indicated that the major Wnt activity early in embryogenesis switched from Wnt3 to Wnt3a around E7.5. The R26‐WntVis mouse line will be widely useful for the study of Wnt signal‐dependent processes. Abstract : We constructed a new Wnt signal reporter, in which HSV‐tk promoter‐driven histone H2B‐EGFP was inserted in the ROSA26 locus. The R26‐WntVis allele was introduced into Wnt3a −/− and Wnt3a vt/− mutant mouse embryos and compared with wild type embryos to assess its performance. The R26‐WntVis reporter was activated in known Wnt‐dependent tissues and responded in a graded fashion to signal intensity.